"Aviáu enveja de transmetre tres causas" : transmission familiale de l'occitan et idéologies de militants en Provence - Costa, James (My University, 2010)
This article wishes to explore the way in which both language and language transmission in the home are conceptualised among language activists. While it might seem obvious they would be most likely to pass the language on to their own children, this appears not to be such a frequent enterprise. Looking at several narratives collected among language activists in Provence in 2009, I wish to analyse what ideologies lie behind the decisions to use the language as a medium of everyday life within the family – or not. What seems to emerge is the absence of consensus about what 'transmission' means, and this may be due to the recent emergence of the question among militants in Provence. I finally suggest that the very term "transmission" is a metaphor which may in fact preclude certain attitudes. Those might in turn be detrimental to other forms of minority language socialisation in the home.